2016
DOI: 10.21013/jas.v3.n3.p12
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profile of Cutaneous Adverse Drug Reactions in a Tertiary Care Centre

Abstract: Context: Cutaneous adverse drug reactions (cADR) constitute ( 8/71 ;11.3%) and urticaria (5/71 ;7%). Antimicrobials (40.8%), NSAIDS (22.5%) and Antiepileptics (22.5 %) were the common drugs responsible for these eruptions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…This present study showed that the incidence of ACDRs were more in males 55.5% than in females 44.5%, with the male: female ratio 1.25:1. Our study showed male preponderance which was similar to the other studies carried out by Priya Prathap et al, Sharma VK et al, Shah SP et al 10,11,12 Moreover, others' studies like Chatterjee S et al, Sudarshan et al, Nandha R et al showed female preponderance.…”
Section: Discussionsupporting
confidence: 91%
“…This present study showed that the incidence of ACDRs were more in males 55.5% than in females 44.5%, with the male: female ratio 1.25:1. Our study showed male preponderance which was similar to the other studies carried out by Priya Prathap et al, Sharma VK et al, Shah SP et al 10,11,12 Moreover, others' studies like Chatterjee S et al, Sudarshan et al, Nandha R et al showed female preponderance.…”
Section: Discussionsupporting
confidence: 91%
“…7 Prathap et al in India reported 71 cases with ACDR from 14,047 patients over one year, giving a prevalence rate of 0.5%. 8 However, that research included ACDR with all types of hypersensitivity reactions. The study results are influenced by the pharmacogenetic differences on different populations, the freedom to access medicine and healthcare, drugs dosage, use of suspected drugs, and other diseases or comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…6 Other studies also reported that antibiotics, NSAIDs, and antiepileptic drugs were the most frequent drugs that led to ACDR. 7,8 Antimicrobial agents and NSAIDs were considered common agents of ACDR. 5,17 In this study, the most frequent betalactams involved in ACDR were cefadroxil and amoxicillin.…”
Section: Discussionmentioning
confidence: 99%